Weight changes in patients with sustained viral suppression switching tenofovir disoproxil fumarate to tenofovir alafenamide. Issue 6 (8th June 2022) - Schafer, Jason J.; Zimmerman, Matty; Walshe, Ciara; Cerankowski, Jesse; Shimada, Ayako; Keith, Scott W.
Abstract: Objective: Switching from tenofovir disoproxil fumarate (TDF)‐ to tenofovir alafenamide (TAF)‐containing antiretroviral therapy may negatively influence weight, cholesterol, and atherosclerotic cardiovascular disease risk. The extent of these changes and their association with TAF remain unclear. Methods: This retrospective cohort evaluated metabolic changes in virologically suppressed patients with HIV infection who switched from TDF to TAF without switching other antiretroviral therapy medications. Adult patients on TDF and with no HIV viral load values >200 copies/mL for ≥2 years prior to and following a TAF switch were included. Weight and other variables were collected for 2 years before and after the switch. Longitudinal linear mixed‐effects models evaluated changes at 1 and 2 years after the switch. Results: In the unadjusted analysis, there were increases in weight, BMI, total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, triglycerides, systolic blood pressure, fasting glucose, and atherosclerotic cardiovascular disease risk scores 2 years after switching to TAF (each p  ≤ 0.03). However, only increases in total and low‐density lipoprotein cholesterol were associated with TAF and were significantly different from expected changes predicted in the adjusted longitudinal models. Conclusions: Despite observing significant unadjusted metabolic changes after switching to TAF, only changes in cholesterol were associated with TAF and were different from changes expected in time‐trend adjusted models.